MENGEMBANGKAN KREATIFITAS INOVASI DAN PELUANG UNTUK MENUMBUHKAN JIWA ENTREPRENEUR DI ERA DIGITAL PADA SMK YASISKA - Turkamun Turkamun; Ismul Bathni S; Zaki Zaenal Arifin (PENGABDIAN SOSIAL, 2022)
ABSTRACT The development of the creative economy cannot be separated from the younger generation as a "warehouse" of creativity. The younger generation is a productive resource who with creative ideas can open a business (entrepreneur) which also helps the government in reducing the unemployment rate in the productive workforce. increasing national economic development. One form of creativity can be through entrepreneurship. Entrepreneurship is a creative and innovative ability that is used as a basis, tips, and resources to find opportunities for success. Having an entrepreneurial spirit means encouraging an independent, creative, innovative, responsible, disciplined mentality, and not giving up easily, like an entrepreneur when starting his business from the bottom. It would be nice if these traits were carried out on the younger generation who in fact are adventurous souls, full of ideas, and like challenges in general have similarities with the concept of entrepreneurship that answers challenges in general has similarities with the concept of entrepreneurship that answers challenges and takes advantage of opportunities. When there is a Covid 19 Pandemic in Indonesia in 2020, strong enough entrepreneurs are needed to improve the economy of a country. Entrepreneurs must be able to compete and always be able to increase their productivity. One way is through creativity and innovation.The purpose of this community service is to encourage the younger generation to be creative and innovative to support entrepreneurial activities and activities. especially to the teaching staff/teachers and staff of the Yasika Tangsel Vocational School in order to prepare themselves to face global challenges and assist entrepreneurial activities, especially during the pandemic period.For this reason, we from Pamulang University in order to realize the Tridharma of Higher Education will hold outreach to schools around South Tangerang, in carrying out this community service activity we as members of PKM Lecturers of D-III Study Programs, Secretary in collaboration with YASISKA Vocational High School. In this community service, we take the theme: "Developing Creativity, Innovation and Opportunities to Grow Entrepreneurial Spirit in the Digital Era" With this theme, our goal is for the teaching staff/teachers and staff at SMK YASISKA TANGSEL to have human resources who are creative and innovative and passionate. entrepreneur. Keywords: Creativity, Innovative, Entrepreneur  ABSTRAK Perkembangan  ekonomi  kreatif  tidak  dapat  terlepas  dari  generasi  muda  sebagai  “gudang” kreativitas. Generasi  muda  adalah  sumber  daya  produktif  yang  dengan  ide  keratifnya  dapat  membuka  sebuah  usaha  (wirausaha)  yang  juga  membantu  pemerintah  dalam  mengurangi  tingkat  pengangguran  di  angkatan  kerja  produktif.Semakin  banyak  anak  muda  yang  berkecimpung  di  dunia  wirausaha,semakin  banyak  pula  produktifitas  yang  dihasilkan  sehingga  berdampak pula  pada  meningkatnya  perkembangan  ekonomi  nasional. Salah  satu  bentuk  kreatifitas  bisa  melalui  kewirausahaan. Kewirausahaan  adalah  kemampuan  kreatif  dan  inovatif  yang  dijadikan  dasar, kiat, dan  sumber  daya  untuk   mencari  peluang  sukses. Memiliki  jiwa  entrepreneur  berarti  mendorong  adanya  mental  yang  mandiri, kreatif, inovatif, bertanggung  jawab , disiplin, dan  tidak  mudah  menyerah, seperti  layaknya  seorang  wirausahan  ketika  memulai  usahanya  dari  bawah. Alangkah  baiknya  jika  sifat-sifat  ini  dilakukan  pada  generasi  muda  yang  notabenya  adalah  jiwa  petualang, penuh  ide,  dan  menyukai  tantangan  secara  umum  memiliki  kesamaan  dengan  konsep  wirausaha  yang  menjawab  tantangan  secara  umum  memiliki  kesamaaan  dengan  konsep  wirausaha  yang  menjawab  tantangan  dan  memanfaatkan  peluang.  Saat ada Pandemi Covid 19 di Indonesia pada tahun 2020 diperlukan wirausaha-wirausaha yang cukup kuat untuk meningkatkan perekonomian suatu negara. Wirausaha harus dapat bersaing dan selalu bisa untuk menaikkan produktivitasnya. Salah satu caranya adalah dengan kreativitas dan inovasi. Tujuan Pengabdian kepada masyarakat ini untuk mendorong generasi muda agar Kreatif dan Inovatif guna mendukung kegiatan dan aktivitas melakukan berwirausaha. khususnya kepada tenaga pengajar/guru dan staf SMK Yasika Tangsel agar mempersiapkan diri menghadapi tantangan global dan membantu kegiatan kewirausahaan terkhusus pada masa masa pandemic. Untuk itu kami dari Universitas Pamulang dalam rangka mewujudkan Tridharma Perguruan Tinggi akan mengadakan penyuluhan kepada Sekolah-sekolah yang berada disekitar Tangerang Selatan, dalam menjalankan kegiatan pengabdian kepada masyarakat ini kami selaku anggota PKM Dosen Prodi D-III Sekretari bekerjasama dengan Sekolah Menengah Kejuruan YASISKA Dalam kegiatan pengabdian kepada masyarakat ini kami mengambil tema : “Mengembangkan Kreatifitas Inovasi dan Peluang untuk Menumbuhkan Jiwa Entrepreneur di Era Digital di SMK YASISKA” Dengan tema ini tujuan kami adalah agar  para tenaga pengajar/ guru dan staf di SMK YASISKA TANGSEL  memiliki sumber daya manusia yang kreatif dan novaif  dan berjiwa entrepreneur. Kata Kunci : Kreatifitas, Inovatif, Entrepreneur